Challenges of developing and conducting an international study of resilience in migrant adolescents. (March 2020) - Hadfield, Kristin; Ungar, Michael; Emond, Alan; Foster, Kim; Gatt, Justine M; Mason-Jones, Amanda; Reid, Steve; Theron, Linda; Wouldes, Trecia; Wu, Qiaobing
The sequelae of migration and the effects of local migration policies on children's physical and mental health are critical to examine, particularly given the historically high numbers of migrants and displaced people. The vulnerability of the study sample and the need to work across cultures and contexts makes research on this group challenging. We outline lessons learned through conducting a pilot study of resilience resources and mental health among migrant youth in six countries. We describe the benefits and challenges, and then provide recommendations and practical advice for social work researchers attempting cross-cultural team research on migrants.